Implementación de un programa ergonómico para reducir los trastornos musculoesqueléticos en el taller de Master Drilling Perú SAC 2021 - Ruiz Ulloa, Luis Rafhael (2023)
The general objective of the research was to implement an ergonomic program to reduce musculoskeletal disorders in the workshop of Master Drilling Peru 2021. The research was quantitative, pre-experimental design. The population was 6 people. The instruments were the UGT Guide of Catalonia, RM 375 and the REBA Field Sheet. In the first place, the jobs were detected, finding that all the positions evaluated presented ergonomic danger due to lifting loads, repetitive movements and forced postures. Also, risk factors were identified, finding that one of the causes was due to lifting of loads. burden. In addition, according to REBA, the evaluator positions of electrician and quality inspector appeared with a high initial level of 10, and the positions of welder, NDT inspector, and mechanic with a high level of 9, and the job of assistant of cutter, presented an average level of 6. Later, ergonomic improvements were implemented, including an active break program, in addition to hoists and beams in the areas of welding, NDT, mechanics and quality. Finally, after the improvements, the ergonomic risks were reduced, obtaining as a result, according to REBA, a mid-level welder with a final score of 5, NDT and quality inspector, showed a low level of 3, and finally the mechanic positions, electrician and cutter assistant, showed a score of 2.